Treatment burden and the perspectives of patients with psoriasis using topical treatments: results from a national survey of adults with psoriasis in the United States - April Armstrong; Melodie Young; Melissa S. Seal; Robert C. Higham; Teri Greiling (Taylor & Francis Group, 2024)
Background Topical treatments are the foundation for patients with psoriasis; however, adherence can be limited by patient preferences and treatment burden.Methods The Harris Poll conducted an online survey of US patients with psoriasis who use prescription topical therapy to examine their preferences and perspectives on topical treatments.Results Among patients with psoriasis who use topical treatment (n = 507), most participants described their psoriasis symptoms as mild (31%) or moderate (59%). The body areas most often reported to be affected by psoriasis were the scalp, elbows, legs, intertriginous areas, arms, and knees. Participants reported psoriasis affecting the scalp (39%), elbows (20%), and legs (excluding knees; 19%) caused the greatest impact on quality of life. Most participants (76%) preferred topical therapies to treat their psoriasis, while 20% preferred pills, and 4% preferred injections. The most common product attributes that participants wanted in a topical psoriasis treatment and that would help them to continue to use the treatment were: improvement in plaques (68%), itch relief (68%), and easy to apply (63%).Conclusion The respondents to this survey reported that they prefer topical treatments to pills or injections (76%) and most (89%) reported they are interested in trying a new topical treatment.